Analysis of the Impact of Tax Policies and Interest Rates on Company Performance: The Role of Capital Structure Intervention - Zatnika, Yudi; Tresnasari, Rini; Safariah, Iin ? (Program Pascasarjana STIE Amkop Makassar, 2023)
This article presents a comprehensive analysis of the intricate relationships between tax policies, interest rates, capital structure, and company performance within the specific context of BCA KCU Bandung. Through a saturated sampling technique involving 37 employees, the study employs the Structural Equation Modeling (SEM) technique, specifically utilizing SmartPLS analysis. The results indicate that tax policies significantly influence both capital structure and company performance, emphasizing the importance of strategic financial planning in response to changing tax frameworks. Additionally, the study highlights the significant impact of capital structure on company performance, underlining the importance of well-managed debt-equity ratios. In contrast, interest rates did not exhibit a statistically significant direct or indirect impact on company performance in this setting. These findings provide valuable insights for financial managers and policymakers, emphasizing the nuanced nature of financial decision-making and the need for context-specific strategies to optimize company performance in dynamic economic environments. Keywords: Tax Policies, Interest Rates, Company Performance, Capital Structure.